Dispute resolution mechanisms under Investment Treaties and Contracts - Miró Quesada Samanez, Caterina (2022)
The ever-growing importance of foreign investments in international trade has spurred the development of a series of mechanisms to attend to the controversies that may arise during commercial relationships. The authors not only analyze the conflict resolution methods, but also the rights conceded to each individual in the commercial relationship, and the sources from which those rights are born. The authors underline the importance of having a solid and cohesive legal framework before starting any investments in a foreign country, and to that end the Investment Treaties constitute an important structure to reassure the investors that their capital will be protected under every circumstance.